Software Architectures, Components, and Applications - Overhage, S. (Springer, 2017)
The concept of resource architecture has been introduced to describe the association of operations with resources, and interactions between these operations. This paper explains resource architecture with examples, and how it can be used in performance engineering throughout the life of a project.